Effects of gamification and learning styles on English reading comprehension in gendered classrooms - Laura-De La Cruz, Kevin Mario; Quispe Roque, Johann Wilber; Flores Valeriano, Josue William; Mendoza Del Valle , Luz Anabella; Quispe Vargas, Miliam; Quispe Mello, Enrique José (Jurnal Cakrawala Pendidikan, 2026)
The study aims to determine the relationship among gamification, learning styles, and English Reading comprehension within gender-differentiated educational settings, with the goal of understanding how these variables influence reading performance. A quantitative, non-experimental correlational design was applied. The sample consisted of 122 secondary students, equally divided by gender. Surveys and a written test were used to gather data related to the study variables, enabling objective statistical analysis of the relationships among them. The results show no statistically significant differences in English reading comprehension based on gender (p > 0.05). This suggests that gender does not significantly impact reading performance in this population. Instead, the findings suggest that factors such as gamification and learning styles may play a more influential role in improving reading regardless of gender. The study concludes that incorporating gamification strategies and adapting instruction to diverse learning styles can positively motivate students and enhance English comprehension. To achieve greater effectiveness, these strategies should be adjusted to the individual characteristics of learners in gender-differentiated contexts, contributing to more inclusive and efficient educational practices.